2006
DOI: 10.1128/mcb.26.5.1579-1588.2006
|View full text |Cite
|
Sign up to set email alerts
|

Unique Role for the UbL-UbA Protein Ddi1 in Turnover of SCFUfo1 Complexes

Abstract: SCF complexes are E3 ubiquitin-protein ligases that mediate degradation of regulatory and signaling proteins and control G 1 /S cell cycle progression by degradation of G 1 cyclins and the cyclin-dependent kinase inhibitor, Sic1. Interchangeable F-box proteins bind the core SCF components; each recruits a specific subset of substrates for ubiquitylation. The F-box proteins themselves are rapidly turned over by autoubiquitylation, allowing rapid recycling of SCF complexes. Here we report a role for the UbL-UbA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 47 publications
(51 reference statements)
7
81
0
1
Order By: Relevance
“…Such a scenario was supported by overexpression of POF10, probably leading to constitutive occupation of Skp1, which results in lethality (76), and for the Ufo1⌬uim mutant lacking the UIMs. Normally, the UIMs are required for self-ubiquitination of Ufo1; a mutant lacking the UIMs cannot be ubiquitinated anymore and therefore remains in the SCF complex (78). In a variation on self-ubiquitination, Ctf13 is targeted by another F-box protein, Cdc4, when unassembled into a CBF complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scenario was supported by overexpression of POF10, probably leading to constitutive occupation of Skp1, which results in lethality (76), and for the Ufo1⌬uim mutant lacking the UIMs. Normally, the UIMs are required for self-ubiquitination of Ufo1; a mutant lacking the UIMs cannot be ubiquitinated anymore and therefore remains in the SCF complex (78). In a variation on self-ubiquitination, Ctf13 is targeted by another F-box protein, Cdc4, when unassembled into a CBF complex.…”
Section: Discussionmentioning
confidence: 99%
“…Ufo1 itself is also degraded via self-ubiquitination. This ubiquitination reaction is mediated by the ubiquitin interaction motifs (UIMs) in the C terminus of Ufo1 that bind during assembly in the SCF complex to Ddi1, a protein containing ubiquitinlike (UBL) and ubiquitin-associated (UBA) domains (78). Removal of the UIM domain in Ufo1 (Ufo1⌬uim) stabilizes the protein and inhibits the degradation of other proteins normally degraded by SCF complexes.…”
Section: Ufo1: An F-box Protein Involved In Dna Damage Responsementioning
confidence: 99%
“…Ddi1 is composed of at least three domains: an amino-terminal ubiquitin-like domain (UBL), a carboxy-terminal ubiquitin-associated domain (UBA), and an aspartyl protease domain conserved from retroviruses (RVP), which is positioned between the UBL and UBA domains. The UBL domain of Ddi1 shares 16% identity with ubiquitin (Bertolaet et al, 2001b) and was shown to bind to the proteasome (Kaplun et al, 2005); the UBA domain, on the other hand, interacts with ubiquitylated cargoes (e.g., HO endonuclease; Kaplun et al, 2005;Ivantsiv et al, 2006). Therefore, Ddi1, together with other UBL-and UBA-bearing proteins in Saccharomyces cerevisiae (namely, Rad23 and Dsk2), were classified as UBL-UBA ubiquitin receptors that mediate proteasomal degradation of ubiquitylated cargoes (Lambertson et al, 1999;Clarke et al, 2001;Hartmann-Petersen and Gordon, 2004;Elsasser and Finley, 2005;Hicke et al, 2005).…”
Section: Ddi1mentioning
confidence: 99%
“…Rub1 Binds to Non-proteasomal Ub Receptors/ShuttlesThere are three well-studied non-proteasomal Ub receptors/ shuttles: Rad23 (its human orthologue is known as hHR23a) (47,48), Dsk2 (known as hPLIC1 or Ubiquilin 1 (UQ1) in humans) (49), and Ddi1 1 (50,51). All of them are unique in that they contain an N-terminal Ub-like (UBL) domain that binds to the proteasome via Rpn1 (42,52,53) and a C-terminal Ubassociated (UBA) domain that binds to Ub chains (54,55).…”
Section: Rub1 Is Structurally Similar To Ubiquitin-although Rub1 Ismentioning
confidence: 99%